How Good at Neurology are you? – Answers. Issue 6 (1st December 2003) - Goldsmith, Paul; Lennox, Graham; Ray, Julian
Abstract : 1. Tabes Dorsalis. The degree of imbalance is out of proportion to the pain and temperature disturbance, which in conjunction with the eye signs, imply this man's problems are most likely due to proprioceptive abnormalities. His pupils are small and slightly irregular. Such pupils display a light-near dissociation. These are the classic Argyll-Robertson pupils commonly seen in Tabes Dorsalis. The VDRL is often normal in tertiary syphilis, in contrast to the TPHA or microhemagglutinin-treponema pallidum test, which is always positive. Further Reading Carr J (2003) Neurosyphilis. Practical Neurology, 2003, 3, 000–000. Nieman EA (1991) Neurosyphilis yesterday and today. The Journal of the Royal College of Physicians, 25, 321–4. 2. This man has tertiary syphilis with aortitis leading to aortic regurgitation and the diastolic murmur. Unusual patterns of altered sensation may be seen in so called Hitzig zones – the central face, around the nipples, medial forearms, lateral legs and